4-aminobenzoic acid-coated maghemite nanoparticles as potential anticancer drug magnetic carriers: a case study on highly cytotoxic Cisplatin-like complexes involving 7-azaindoles - Starha, Pavel; Stavárek, Martin; Tuček, Jiří; Trávníček, Zdeněk (Molecules (Basel, Switzerland), 2014)
This study describes a one-pot synthesis of superparamagnetic maghemite-based 4-aminobenzoic acid-coated spherical core-shell nanoparticles (PABA@FeNPs) as suitable nanocomposites potentially usable as magnetic carriers for drug delivery. The PABA@FeNPs system was subsequently functionalized by the activated species (1* and 2*) of highly in vitro cytotoxic cis-[PtCl2(3Claza)2] (1; 3Claza stands for 3-chloro-7-azaindole) or cis-[PtCl2(5Braza)2] (2; 5Braza stands for 5-bromo-7-azaindole), which were prepared by a silver(I) ion assisted dechlorination of the parent dichlorido complexes. The products 1*@PABA@FeNPs and 2*@PABA@FeNPs, as well as an intermediate PABA@FeNPs, were characterized by a combination of various techniques, such as Mössbauer, FTIR and EDS spectroscopy, thermal analysis, SEM and TEM. The results showed that the products consist of well-dispersed maghemite-based nanoparticles of 13 nm average size that represent an easily obtainable system for delivery of highly cytotoxic cisplatin-like complexes in oncological practice.
Keywords: indoly; Nanoparticles; Humans; 4-Aminobenzoic Acid; Indoles; cisplatina; Cisplatin; Drug Carriers; Antineoplastic Agents; Drug Delivery Systems; lidé; Silver; Ferric Compounds; stříbro; lékové transportní systémy; Neoplasms; nanočástice; nosiče léků; železité sloučeniny; protinádorové látky; nádory; kyselina 4-aminobenzoová